Regulation of blood-testis barrier dynamics by focal adhesion kinase (FAK): An unexpected turn of events - Cheng, C. Yan (2009)
The blood-testis barrier (BTB) is conferred by co-existing tight junctions (TJs), basal ectoplasmic specializations (basal ES), desmosome-like junctions and gap junctions (GJs) between adjacent Sertoli cells near the basement membrane in the seminiferous epithelium. While the concept of the BTB has been known for more than a century and its significance to spermatogenesis discerned for more than five decades, its regulation has remained largely unknown. Recent studies, however, have demonstrated that focal adhesion kinase (FAK), a modulator of the integrin-based signaling that plays a crucial role in cell movement, apoptosis, cell survival and gene expression at the focal adhesion complex (FAC, also known as focal contact, a cell-matrix anchoring junction type), is an integrated component of the BTB, associated with the TJ-integral membrane protein occludin and its adaptor zonula occludens-1 (ZO-1). Herein, we summarize recent findings in the field regarding the significance of FAK in conferring BTB integrity based on some unexpected observations. We also critically discuss the role of FAK in regulating the timely “opening” and “closing” of the BTB to facilitate the transit of primary preleptotene spermatocytes across the BTB at stage VIII of the seminiferous epithelial cycle of spermatogenesis. Lastly, we describe a working model, which can be used to design future functional experiments to explore the involvement of FAK in BTB dynamics by investigators in the field.